2023
DOI: 10.1136/bmjopen-2022-064347
|View full text |Cite
|
Sign up to set email alerts
|

Self-management in adults after solid-organ transplantation: a scoping review protocol

Abstract: IntroductionAfter solid-organ transplantation (SOTx), recipients must adhere to a lifelong medical regimen, change their lifestyle and cope with physiological and psychosocial challenges. This requires active participation in their care and self-management abilities. The concept of self-management after SOTx has only been described regarding specific organs and focused on adherence to medical treatment. A comprehensive conceptualisation of self-management entailing all solid organs and beyond medical aspects d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 82 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…In brief, the initial set of definitions from the SMART study scoping review conducted from inception to September 2021 was obtained. A protocol detailing the SMART study search design has been published elsewhere [ 36 ]. The SMART study scoping review included 742 records (initially 34.045 records from database and supplementary searches).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In brief, the initial set of definitions from the SMART study scoping review conducted from inception to September 2021 was obtained. A protocol detailing the SMART study search design has been published elsewhere [ 36 ]. The SMART study scoping review included 742 records (initially 34.045 records from database and supplementary searches).…”
Section: Methodsmentioning
confidence: 99%
“…This study applied a second screen to the definitions identified from the included 742 SMART study records containing a definition of SM for SOTx. The broader SMART study eligibility criteria focused on published articles on self-management of challenges and needs, published in English or German reporting on adults after SOTx, that is, heart, lung, liver, pancreas, kidney, or small bowel transplantation; it is reported in full elsewhere [ 36 ]. We aimed to identify definitions of self-management (including the term self-management support) but not associated concepts such as self-efficacy or self-care.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations